The Potential of Organic Vegetable from Peat Swamp Land in Central Kalimantan as Fungicide and Bactericide - Yanetri Asi Nion; Kamilah Kamilah (Journal of Wetlands Environmental Management, 2023)
The research was to determine the potential of various species of organic vegetable from bamboo, taro, rattan and eggplant group from Central Kalimantan as fungicide and bactericide. In vitro testing of botanical pesticides used two types of fungi, namely Colletotrichum capsici and Sclerotium roflsii), and one pathogenic bacteria, namely Xanthomonas campestris. The results showed that several organic vegetable extracts from taro and rattan could control C. capsici, S. roflsii and X. campestris. It was proven that extract plant from immature fruit of Solanum ferox, mature fruit of S. lasiocarpum, leaf of S. torvum, tuber of Xanthosoma sagittifolium, leaf and midrib of Colocasia esculenta, C. esculenta and C. esculenta, fresh leaf of Dendrocalamus asper, stem inside of rattan Calamus trachycoleus  and Daemonorops fissa against growth of S. rolfsii. It was also found that four type of plant extracts could control C. capsici (that is fresh leaf of S. lasiocarpum and S. torvum, tuber of C. esculenta, leaf and midrib of X. sagittifolium). This study was the first to report that plant extracts from fresh leaf and mature fruit of S. ferox, mature fruit of S. melongena, leaf and midrib of C. esculenta, fresh leaf and stem of D. asper, stem of B. vulgaris var striata, skin and stem inside of C. trachycoleus and skin of D. fissa can inhibit growth of X. campestris bacteria. Hance, non-vegetable and organic vegetables from Central Kalimantan had potential as botanical pesticides.